Framing a new discourse on the notion of habitat in transforming societies - Sedighi, Mohamad; Varma, Rohan (International Planning History Society Proceedings, 2018)
This paper reveals how the second Iran International Congers of Architects (IICA), held in Persepolis- Shiraz in 1974, and the first UN Habitat conference, held in Vancouver, Canada in 1976 played an instrumental role in shaping a discourse on the notion of regionalism in the design for human habitats, especially in developing countries. Building upon a brief analysis of the works of Nader Ardalan, Kamran Diba, Charles Correa, Balkrishna Vithaldas Doshi and Raj Rewal, this paper discussed the incorporation of the ideas published in the Habitat Bill of Rights within their private commissions for large scale housing schemes and master plans in their respective countries, Iran and India. More crucially, this paper argues that both events helped bring together these architects who later, in different capacities, played significant roles as members of the Aga Khan Award for Architecture in fostering and promoting an alternative way of adapting modernism to industrializing countries.